RELAÇÃO ENTRE RESISTÊNCIA À INSULINA E ESTRESSE OXIDATIVO EM IDOSAS PARTICIPANTES DE GRUPOS DE CONVIVÊNCIA DA CIDADE DE SANTA MARIA/RS. - Queiroz, Jeferson Lopes (2018)
Introduction: In recent decades, changes in the behavioral, social and economic patterns of the Brazilian population have reflected in the increase in life expectancy. Individuals with comorbidities such as obesity and type 2 diabetes melittus are susceptible to several metabolic changes, such as: atherosclerosis, arterial hypertension, dyslipidemia, insulin resistance, oxidative stress between Others, increasing the risk of cardiovascular accident. Objective: To investigate the relation of insulin resistance and the markers of oxidative stress in elderly participants of coexistence groups of the city of Santa Maria/RS. Methodology: It is a transversal study, with a sample of 105 elderly women. Blood samples were collected for the laboratory dosages of oxidative stress markers and biochemical analyses. The participants had a anthropometric evaluation (weight, height, abdominal circumference) and blood pressure verification. The detection of insulin resistance was determined by the use of the mathematical methods of HOMA β, HOMA – IR and Quicki and the activity of oxidative stress was evaluated by dosage of the enzymes, NPSH and reactive substances to acid Thiobarbituric (TBARS). Results: Positive associations were found between the HOMA-IR and Quicki with the metabolic parameters associated with obesity. The positive association between NPSH levels and HOMA β was also found, where older women with lower insulin sensitivity showed higher levels of NPSH markers, indicating the need for greater action of the antioxidant defense system in Reactive oxygen species combat, thus avoiding oxidative stress. In the other markers of oxidative stress, activity of CAT and TBARS, no significant differences were found in the elderly with insulin resistance. Conclusion: Associations were found between insulin resistance and metabolic parameters associated with obesity, and the positive relationship between the levels of NPSH and insulin sensitivity through the HOMA β, indicating that the lower the sensitivity to insulin, the greater It will be the presence of reactive oxygen species. In the markings of 9 the activity of the lipid and in the levels of peroxidation, we do not find significant differences between the sample groups